Effects of Dexmedetomidine-Fentanyl Infusion on Blood Pressure and Heart Rate during Cardiac Surgery in Children - Jyrson Guilherme Klamt; Walter Villela de Andrade Vicente; Luis Vicente Garcia; Cesar Augusto Ferreira (Anesthesiology Research and Practice)
Background. The purpose of this study was to access the effects of dexmedetomidine-fentanyl infusion on blood pressure (BP) and heart rate (HR) before surgical stimulation, on their changes to skin incision, and on isoflurane requirement during cardiac surgery in children. Methods. This study had a prospective, randomized, and open-label design. Thirty-two children aged 1 month to 10 years undergoing surgery for repair congenital heart disease (CHD) with CPB were randomly allocated into two groups: group MDZ received midazolam 0.2 mg·kg−1·h−1 and group DEX received dexmedetomidine 1 𝜇g·kg−1·h−1 during the first hour followed by half of these rates of infusions thereafter. Both group received fentanyl 10 𝜇g·kg−1, midazolam 0.2 mg·kg−1 and vecuronium 0.2 mg·kg−1 for induction. These same doses of fentanyl and vecuronium were infused during the first hour then reduced to half. The infusions started after induction and maintained until the end of surgery. Isoflurane was given briefly to control hyperdynamic response to skin incision and sternotomy. Results. In both groups, systolic blood pressure (sBP) and heart rate (HR) decreased significantly after one hour of infusion of the anesthetic solutions, but there were significantly less increase in diastolic blood pressure, sBP, and HR, and less patients required isoflurane supplementation to skin incision in the patients of the DEX group. Discussion. Dexmedetomidine infusion without a bolus appears to be an effective adjunct to fentanyl anesthesia in control of hemodynamic responses to surgery for repair of CHD in children.